7. x + b/2a = +/- sqrt((b^2 - 4ac)/4a^2)
8. x = -b/2a +/- sqrt((b^2 - 4ac)/4a^2)
9. x = (-b +/- sqrt(b^2 - 4ac)) / 2a
These three steps simplify the expression from step 6 and derive the quadratic formula.
The first six steps of the derivation of the Quadratic Formula are listed below.
1. ax^2 + box + c = 0
2. (((a/a)x)^2) + ((b/a)x) + c/a = 0/a
3. x^2 + ((b/a)x) + c/a = 0
4. x^2 + ((b/a)x) = -(c/a
5. x^2 + ((b/a)x) + (b^2)/4a^2 = - c/a + (b^2)/4a^2
6. (x + b/2a)^2 = (b^2 - 4ac)/ 4a^2
what are the next 3 steps
1 answer